THE JOURNEY OF LIFE AND CREATIVITY "KEMAS ANWAR BECK" THE ARTIST OF PLEMBANG BAGHI - Irawan Sukma (JURNAL PAKARENA, 2021)
The article entitled “The journey of life and creativity of Kemas Anwar Beck the PlembangBaghi artists” was theoretically encouraged to understand the aspects of the work, thought and success of the package of Kemas Anwar Beck’s natural talent. The choise pf Yaii Beck is a close call for Kemas Anwar Beck as a research subject because he is a skilled and successful atists with many skills, who created Palembang songs and dance traditions of South Sumatera and did an understanding of smooth Palembang remains intact. The author approaches psichology directly through interviews using theoretical and multiple concepts in humanities and social sciences. The results of the study revealed that Kemas Anwar Beck is the one who successfully contributed his work to the development of the art in South Sumatera.